Challenges of modern medicine – a case study of a patient with ALS after age 60 - Kasperska, Paulina; Oleksy, Eliza; Ziółkowska, Anna; Stemplowski, Wojciech; Sokołowski, Remigiusz; Klimkiewicz-Wszelaki, Karolina; Zukow, Walery; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
Background. Amyotrophic lateral sclerosis is a degenerative disease of the nervous system, neurodegenerative cerebral cortex, pad and spinal cord due to damage to the upper and lower motor neurons, with progressive course, various symptoms with varying intensity and duration (from several months to even 10 years), extremely unfavorable prognosis. As an incurable and progressive disease, due to the deterioration of mobility it leads to complete stopping of muscles, including respiratory ones, with the intellectual ability of the patients fully preservedCase report. A 65-year-old patient was hospitalized in Geriatrics Clinic in University Hospital A. Jurasza in Bydgoszcz. Patient with shortness of breath, present paradoxical chest movement, impaired chest mobility, present whirring, wheezing during auscultation examination. The patient was admitted to the ward because of pneumonia. Amyotrophic lateral sclerosis, chronic respiratory failure, hypertension, and hyperthyroidism were diagnosed. In the medical history she had swallowing problems, abdominal pain, insufficient cough reflex, dysphagia, increased body temperature, difficulty falling asleep, depressed mood. The patient did not consent to a tracheotomy for aspiration of secretions from the respiratory tract. The patient required suctioning of excessively accumulating secretions in the mouth. The patient was patted. Patient's skin without pathological changes. During the night, the patient requires non-invasive mechanical ventilation - BIPAP respirator. Patient under the care of the Palliative Medicine Clinic. Patient fed an industrial diet (Isosource Protein) for PEG (percutaneous endoscopic gastrostomy) - self-service.Results. Although the disease is incurable, many of its symptoms can be alleviated, and the goal of therapy should be to improve the quality of life and maintain patient independence for as long as possible. SLA patients and their relatives often experience depression, feelings of despair and anxiety. Therefore, psychological help is recommended for patients and their relatives. The continuous development of medicine remains a hope for this disease. There is a need to continue research into the search for an effective cure for amyotrophic lateral sclerosis.